The Relationship between Nutritional Status and Physical Activity with Blood Pressure in Children Aged 16-18 Years at SMA Negeri 7 Samarinda - Istikawati, Endah; Lamri, Lamri; Utami, Kurniati Dwi (East Asian Journal of Multidisciplinary Research, 2024)
High blood pressure is often seen as a common health problem in the elderly. However, recent findings suggest that adolescents can also experience hypertension. Hypertension that occurs in adolescence tends to continue into adulthood. This study aims to determine the relationship between nutritional status and physical activity and blood pressure in students aged 16-18 years at SMA Negeri 7 Samarinda. This study uses a quantitative approach with a cross-sectional design, conducted in February 2024 involving 56 respondents. The results of the analysis using the Pearson Chi-Square Test showed a significant relationship between nutritional status (p=0.032) and physical activity (p=0.011) and blood pressure in this age group. Thus, it is important to pay attention to diet and physical activity to reduce the risk of hypertension and health complications in adulthood.